Injecting NMDA and Ro 25‐6981 in insular cortex induce neuroplastic changes and neuropathic pain‐like behaviour. (2nd July 2018) - Yoon, M.S.; Koh, C.S.; Lee, J.; Shin, J.; Kong, C.; Jung, H.H.; Chang, J.W.
Abstract: Background: Neuropathic pain is associated with abnormal sensitivity of the central nervous system. Although the mechanism underlying the development of sensitization remains to be fully elucidated, recent studies have reported that neuroplastic changes in the pain circuitry may be involved in hypersensitivity associated with neuropathic pain. However, it is difficult to investigate such phenomena in existing animal pain model. Therefore, in this study, we developed a novel animal model – the circuit plasticity reconstruction (CPR) model – to mimic central sensitization associated with neuroplastic changes. Method: NMDA and Ro 25‐6981 were injected into the right insular cortex of Sprague‐Dawley rats, while electrical stimulation was delivered to the contralateral hind paw. Mechanical allodynia was tested by von Frey test with up–down method, and neuroplastic changes were confirmed by PSA‐NCAM‐positive immunostaining. Result: The mechanical withdrawal threshold of the left hind paw decreased beginning 1 day after CPR modelling and persisted until day 21 comparing to the modified CPR 1 (mod‐CPR 1) group (CPR: 91.68 ± 1.8%, mod‐CPR 1: 42.71 ± 3.4%, p < 0.001). In contrast, mod‐CPR 2 surgery without electrical stimulation did not induce mechanical allodynia. Immunostaining for PSA‐NCAM also revealed that neuroplastic changes had occurred in the CPR group. Conclusion: Our results demonstrated that CPR modelling induced neuroplasticity within the insular cortex, leading to alterations in the neural circuitry and central sensitization. Significance: This article represents that the CPR model can mimic the neuropathic pain derived by neuroplastic changes. Our findings indicate that the CPR model may aid the development of novel therapeutic strategies for neuropathic pain and in elucidating the mechanisms underlying pain induced by central sensitization and neuroplastic changes.